2020
DOI: 10.1021/acs.chemrestox.0c00064
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Profiles of Smokers from Two Ethnic Groups with Differing Lung Cancer Risk

Abstract: African American (AA) smokers are at a higher risk of developing lung cancer compared to whites. The variations in the metabolism of nicotine and tobacco-derived carcinogens in these groups were reported previously with the levels of nicotine metabolites and carcinogen-derived metabolites measured using targeted approaches. While useful, these targeted strategies are not able to detect global metabolic changes for use in predicting the detrimental effects of tobacco use and ultimately lung cancer susceptibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…It has been reported that the accumulation of pyroglutamic acid could result in metabolic acidosis, which might promote stone formation ( Wagner and Mohebbi, 2010 ; Weiler et al., 2015 ). The other three metabolites were found to correlated with nicotine metabolism, anti-inflammation, and lipid metabolism ( Tan et al., 2019 ; Dator et al., 2020 ; Wojcieszyńska and Guzik, 2020 ). However, no related studies have reported the relationship between these metabolites and kidney stones, which should be investigated further to characterize their roles in the disease.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the accumulation of pyroglutamic acid could result in metabolic acidosis, which might promote stone formation ( Wagner and Mohebbi, 2010 ; Weiler et al., 2015 ). The other three metabolites were found to correlated with nicotine metabolism, anti-inflammation, and lipid metabolism ( Tan et al., 2019 ; Dator et al., 2020 ; Wojcieszyńska and Guzik, 2020 ). However, no related studies have reported the relationship between these metabolites and kidney stones, which should be investigated further to characterize their roles in the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The ethnicity of the subject can also have an impact on metabolic signatures. For example, differences in the profiles of individual smokers were noted between African Americans and Caucasians [51].…”
Section: Sex Age and Ethnicitymentioning
confidence: 99%
“… 19 23 Although comprehensive analysis is provided, multi-separation approaches can be time-consuming and laborious, sometimes requiring extensive sample preparation procedures. Several single metabolomics methods have been developed for, e.g., plasma and urine analysis, with excellent results (see, e.g., refs ( 24 ) and ( 25 )). Broad range single methods are even beginning to merge different omics; He et al have recently combined lipidomics and proteomics with a single-shot technology.…”
Section: Introductionmentioning
confidence: 99%
“…A key challenge with analyses of biological samples is the wide polarity range of clinically relevant metabolites, ranging from, e.g., hydrophobic fatty acids to polar amino acids, often addressed by using several analytical methods/platforms, e.g., employing gas chromatography in addition to hydrophilic interaction liquid chromatography (HILIC) and reversed phase LC, to cover a broad part of the metabolome. Although comprehensive analysis is provided, multi-separation approaches can be time-consuming and laborious, sometimes requiring extensive sample preparation procedures. Several single metabolomics methods have been developed for, e.g., plasma and urine analysis, with excellent results (see, e.g., refs and ). Broad range single methods are even beginning to merge different omics; He et al have recently combined lipidomics and proteomics with a single-shot technology .…”
Section: Introductionmentioning
confidence: 99%